Pengaruh Online Customer Rating dan Online Customer Reveiw Terhadap Keputusan Pembelian Pada Marketplace (Studi Kasus Mahasiswa Program Studi Pendidikan Ekonomi Fakultas Keguruan dan Ilmu Pendidikan Universitas Jember) - Dwi Aprilia (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study aims to investigate the influence of Online Customer Rating and Online Customer Review on purchasing decisions in marketplaces among students of the Economics Education Study Program, Faculty of Teacher Training and Education, University of Jember, Class of 2024. A quantitative research method with a survey approach was employed. The research population comprised all students of the Economics Education Study Program at the University of Jember, Class of 2024, with a total of 100 respondents. Data were collected through questionnaires disseminated via Google Form. The results indicate that Online Customer Rating has an influence of 32.80% on purchasing decisions, while Online Customer Review contributes 55.09% to purchasing decisions. Simultaneously, Online Customer Rating and Online Customer Review collectively contribute 87.9% to the variance in purchasing decisions. These findings suggest that both variables play a highly significant role in influencing consumer behavior in online marketplaces. The implications of this study can serve as a foundation for marketplaces and sellers to optimize their marketing strategies and build consumer trust through the effective management of reviews and ratings.
Reaploud Repository April 2026
Keywords: Online Customer Rating; Online Customer Review; Purchasing Decision; Marketplace.